To be or not to be an auxiliary verb. The case of Spanish - Vivanco, Margot (Borealis – An International Journal of Hispanic Linguistics, 2019)
This paper studies two Spanish constructions with the verb poner (‘to put’) and an infinitive. The first one, , has  traditionally been considered an inchoative periphrasis; however, we will show that its grammaticalisation is only complete with inanimate or impersonal subjects, while with animate subjects the structure keeps causative semantics. The second one, , has received much less attention in the literature. Although it originated together with its se-counterpart, it has not become a periphrasis and today exhibits a hybrid behaviour similar to that of verbs of influence on the one hand and restructuring causative verbs on the other. It will be shown that both constructions started with a causative-aspectual meaning (‘triggering an event’) that they keep today: ponerse has a causative meaning despite being an auxiliary and poner has an aspectual meaning despite not being an auxiliary, which explains many of their special characteristics. This paper will not only shed light on the diachronic and synchronic properties of these constructions but will also reflect on the limits between lexical and grammatical categories.
Keywords: verbal periphrasis; grammaticalisation; causativity; aspect